The Impact of Product Quality on Purchase Decisions Following a Fuel Fraud Scandal: The Mediating Role of Consumer Trust in Madiun Regency, Indonesia - Argita Septiana; Yulia Anggraini (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2026)
A fuel fraud scandal involving fraudulent practices has caused financial losses and eroded consumer trust in the Madiun Regency, Indonesia. This study aims to analyze the influence of product quality on consumer trust and fuel purchasing decisions in the aftermath of the scandal, with consumer trust as a mediating variable. This quantitative study employed convenience sampling of 200 respondents from the Muslim community in Madiun Regency, with data collection conducted in November 2025. Data analysis was conducted using the SEM-PLS. The results indicate that product quality has a positive and significant effect on consumer trust (β = 0.451) and purchase decisions (β = 0.414), whereas consumer trust significantly influences purchase decisions (β = 0.307). Testing for indirect effects showed that consumer trust partially mediates the relationship between product quality and purchase decisions (β = 0.127). The results show that product quality and trust are important factors influencing post-scandal purchasing behavior. These findings have practical implications for companies and the government to improve transparency and quality control, as well as help consumers make more informed and safer purchasing decisions.